Topologically charged BPS microstates in AdS3/CFT2 - Arash Arabi Ardehali; Hare Krishna (Journal of High Energy Physics)
Abstract In the standard N $$ \mathcal{N} $$ = (4, 4) AdS3/CFT2 with sym N (T 4), as well as the N $$ \mathcal{N} $$ = (2, 2) Datta-Eberhardt-Gaberdiel variant with sym N (T 4/ℤ 2), supersymmetric index techniques have not been applied so far to the CFT states with target-space momentum or winding. We clarify that the difficulty lies in a central extension of the SUSY algebra in the momentum and winding sectors, analogous to the central extension on the Coulomb branch of 4d N $$ \mathcal{N} $$ = 2 gauge theories. We define modified helicity-trace indices tailored to the momentum and winding sectors, and use them for microstate counting of the corresponding bulk black holes. In the N $$ \mathcal{N} $$ = (4, 4) case we reproduce the microstate matching of Larsen and Martinec. In the N $$ \mathcal{N} $$ = (2, 2) case we resolve a previous mismatch with the Bekenstein-Hawking formula encountered in the topologically trivial sector by going to certain winding sectors.